Critical Analysis of Apixaban Dose Adjustment Criteria. (1st June 2021) - Vu, Anh; Qu, Tao T.; Ryu, Rachel; Nandkeolyar, Shuktika; Jacobson, Alan; Hong, Lisa T.
Apixaban is indicated for the prevention of ischemic stroke in non-valvular atrial fibrillation (NVAF), as well as for the prevention and treatment of venous thromboembolism (VTE). Dose adjustment is based on age, weight, and serum creatinine in NVAF, while there are no recommended adjustment criteria for VTE. Such adjustment is unconventional compared to other commonly used medications. The objective of this manuscript is to critically analyze each apixaban dosing adjustment criterion and its associated outcomes. PubMed articles from March 2013 to March 2020 were selected with search terms "apixaban, " and "dose adjustment, " "adjustment, " or "adjustment criteria." Pharmacokinetic studies demonstrated increased apixaban exposure in patients >65 years of age, those with extreme body weights, and those with advanced renal impairment, though post-hemodialysis dosing may off-set the elevated apixaban exposure. However, clinical data show that among patients> 75 years, < 60 kg, and with estimated glomerular filtration rate <50 mL/min, including those on dialysis, there is no reduction in apixaban safety or efficacy. Published literature describes variable dosing strategies utilized in clinical practice. Overall, apixaban dose adjustment criteria may need to be re-evaluated.